2014
DOI: 10.1039/c4md00124a
|View full text |Cite
|
Sign up to set email alerts
|

Thiazole-based aminopyrimidines and N-phenylpyrazolines as potent antimicrobial agents: synthesis and biological evaluation

Abstract: A series of eight thiazole-based N-phenylpyrazolines and two aminopyrimidines having several chalcone derivatives as precursors have been synthesized and evaluated for their antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In particular, thiazole is a well-known heterocyclic aromatic compound that contains sulfur and nitrogen atoms at positions 1 and 3 of its five-member ring, respectively [ 20 ]. Τhiazole moiety can be found in numerous biologically active compounds of natural origin (e.g., thiamine [ 19 , 20 ], mycothiazole [ 21 ], cystothiazole C [ 22 ], as well as synthetic molecules possessing a wide range of pharmacological activities such as antimicrobial [ 23 , 24 , 25 , 26 , 27 , 28 ], antiviral [ 29 , 30 ], antitubercular [ 23 , 31 ], anti-inflammatory [ 32 , 33 , 34 ], anxiolytic [ 35 ], anaesthetic [ 36 ], anticonvulsant [ 37 , 38 , 39 , 40 ], etc.). There is a large number of known marketed drugs containing thiazole rings, such as the anthelmintic tiabendazole, the antibacterial sulfathiazole, the anticonvulsant riluzole, the anti-ulcer alizatidine, the antiparkinsonian talipexole, the antischistosomal niridazole, the antiviral ritonavir and the anti-inflammatory meloxicam.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, thiazole is a well-known heterocyclic aromatic compound that contains sulfur and nitrogen atoms at positions 1 and 3 of its five-member ring, respectively [ 20 ]. Τhiazole moiety can be found in numerous biologically active compounds of natural origin (e.g., thiamine [ 19 , 20 ], mycothiazole [ 21 ], cystothiazole C [ 22 ], as well as synthetic molecules possessing a wide range of pharmacological activities such as antimicrobial [ 23 , 24 , 25 , 26 , 27 , 28 ], antiviral [ 29 , 30 ], antitubercular [ 23 , 31 ], anti-inflammatory [ 32 , 33 , 34 ], anxiolytic [ 35 ], anaesthetic [ 36 ], anticonvulsant [ 37 , 38 , 39 , 40 ], etc.). There is a large number of known marketed drugs containing thiazole rings, such as the anthelmintic tiabendazole, the antibacterial sulfathiazole, the anticonvulsant riluzole, the anti-ulcer alizatidine, the antiparkinsonian talipexole, the antischistosomal niridazole, the antiviral ritonavir and the anti-inflammatory meloxicam.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of a large number of antibiotics and chemotherapeutics, the increasing clinical importance of drug-resistant microbial pathogens have lent additional urgency in microbiological and antifungal research [1e4]. They display quite a broad spectrum of biological activities [6], which have found applications in the treatment of allergies [7], hypertension [8], inflammation [9], schizophrenia [10], microbial infections [11,12], HIV infections [13], hypnotics [14] and pain [15]. In this context, thiazole derivatives have been playing a crucial role in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 38 inhibited the growth of all pathogens tested (MIC 31.25 µg/mL for Gram-positive bacteria), which might be due to the presence of a 3-carbamoyl-4-hydroxy-phenyl group [83]. Liaras et al (2014) produced and tested a variety of amino-pyrimidine derivatives based on thiazoles for antibacterial activity. The synthesis of aimed N-phenylpyrazolines and amino-pyrimidines was afforded by heterocyclization of the corresponding chalcones with phenylhydrazine hydrochloride and guanidine hydrochloride in the presence of sodium hydroxide.…”
Section: Thiazoles As Antimicrobial Agentsmentioning
confidence: 99%
“…Molecules 39a and 39b showed a better activity profile when compared to the reference drugs ampicillin and streptomycin. The SAR analysis revealed that the presence of NHCH 3 and a phenyl group on the side chain are essential for the activity [84]. Some novel thiazole compounds have been identified as promising antibacterial agents in a recent investigation.…”
Section: Thiazoles As Antimicrobial Agentsmentioning
confidence: 99%